Pembelajaran Matematika Dalam Membentuk Karakter Siswa Berpikir Kreatif - Fitrofa, Fitrofa; Peni, Nur Robiah Nofikusumawati (Sepren, 2024)
The success of nurturing a high-quality generation within a nation transcends mere academic achievements. The educational journey is envisioned as a crucial avenue for cultivating individuals with robust moral values applicable to their daily lives. Within the educational framework, mathematics holds a pivotal role in shaping students' character. To effectively in still character-building values, educators must craft well-designed learning experiences in mathematics. It is envisaged that through mathematical learning, students develop virtues such as diligence, critical thinking, and creativity. Mathematics, characterized by deductive reasoning, inherently fosters creative thinking among students. In daily life, the cognitive process of problem-solving underscores the significance of creative thinking, which involves synthesizing various patterns and approaches. Creative thinking finds practical application in tackling mathematical challenges, leading to the emergence of innovative solutions. Hence, by engaging in mathematics education, students are poised to embrace a character marked by ingenuity and inventive problem-solving abilities.